2021
DOI: 10.1108/ijppm-01-2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing barriers for the adoption of circular economy in the manufacturing sector

Abstract: PurposeThe operational activities of manufacturing organizations are continuously degrading the environment. Circular economy adoption can help industries optimize their resources along with minimal waste generation. The purpose of this study is to identify and analyze the barriers that hinder the adoption of circular economy (CE) in the manufacturing sector.Design/methodology/approachThe barriers are extracted from a critical review of the literature and listed into three categories as social, economic and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 48 publications
1
18
0
2
Order By: Relevance
“…The finding of this study supports the previous research from Rhein & Strater (2021;Singh et al, 2018;Moktadir et al, 2020;Badhotiya et al, 2021;Daddi, 2018) which statted that environmental commitment has a positive and significant influence on circular economy implementation. Table 6 show the result that the t-statistic value of environmental commitment on circular economy implementation is 3.989 > 1.96 with the p-value of 0.000 < 0.05, thus hypothesis 2 is accepted.…”
Section: The Influence Of Environmental Commitment On Circular Econom...supporting
confidence: 90%
See 2 more Smart Citations
“…The finding of this study supports the previous research from Rhein & Strater (2021;Singh et al, 2018;Moktadir et al, 2020;Badhotiya et al, 2021;Daddi, 2018) which statted that environmental commitment has a positive and significant influence on circular economy implementation. Table 6 show the result that the t-statistic value of environmental commitment on circular economy implementation is 3.989 > 1.96 with the p-value of 0.000 < 0.05, thus hypothesis 2 is accepted.…”
Section: The Influence Of Environmental Commitment On Circular Econom...supporting
confidence: 90%
“…The study carried out by Singh et al (2016;Rhein & Strater, 2021;Moktadir et al, 2020;Badhotiya et al, 2021;Daddi, 2018) showed a significant influence of environmental commitment on circular economy readiness. Lack of environmental commitment in the organization will be an obstacle in adopting circular economy.…”
Section: Circular Economy Implementation As Mediating Variablementioning
confidence: 98%
See 1 more Smart Citation
“…These barriers are divided into three criteria, namely social, economic, and environmental. Badhotiya et al, (2021) state that the social barrier criteria have the highest importance among the three criteria. There is a hierarchy of barriers to the lack of top management commitment within the social criteria.…”
Section: Environmental Commitmentmentioning
confidence: 99%
“…This paper, therefore, aims to fill the literature gap regarding the role played by smart manufacturing techniques in the adoption of circular economy practices [42], and how to transform part of Big Data into Smart Data [39], focusing on the re-engineering of the product and input sourcing system in an operational environment with a quantitative approach [41]. To achieve this goal, the study analyzes the manufacturing process of ceramic tiles for construction in Italy, a resource-intensive industry [43] with a complex input sourcing system [44], a high level of adoption of Industry 4.0 digital technologies [45,46], and characterized by the implementation of internationally recognized environmental best practices [11].…”
Section: Introductionmentioning
confidence: 99%